Improving Nurses Knowledge and Practices of Delirium Assessment at Mbarara Regional Referral Hospital: A Quasi Experimental Study - Murungi, Eric Baluku; Niyonzima, Vallence; Atuhaire, Eva; Nantume, Susan; Beebwa, Esther (Advances in Medical Education and Practice, 2023)
Background: Despite the recommendations for delirium assessment in clinical settings, it stills remain a serious clinical problem associated with prolonged mechanical ventilation, stress on the patient and family, and mortality. There is paucity of data regarding delirium assessment and prevention in developing world. The Confusion Assessment Method for Intensive Care Unit (CAM-ICU) was developed to aid in the assessment of delirium. There is no documented assessment of delirium and prevention in Uganda. This study evaluated the effect of an educational intervention on nurses’ knowledge and practices of delirium assessment using the CAM–ICU tool. Methods: We used a quasi-experimental and recruited a convenience sample of 29 nurses from ICU and ER. The assessment before and after the interventions was conducted using a self-completed questionnaire from October 2020 to January 2021. The interventions were delivered through face-to-face presentations, demonstrations, watching videos, and hands on practice. Data were entered into excel, cleaned and exported to Stata version 14. Median and interquartile ranges were used for continuous variables, and frequencies and percentages for categorical variables. The mean knowledge score was calculated before and after the intervention. A paired t-test was used to compare Pre- and Post-test knowledge and practice scores at P <0.05. Results: Majority (62%) were female, 48% were Diploma holders, median age was 30 (IQR = 28–32) years and median years of experience 3.5 (IQR = 3–4). The Mean knowledge scores was 10.7 (SD = 2.36) pretest and 19 (0.94) posttest. The mean practice score was 2 (SD = 0.83) pretest and 6 (0.35) posttest. There were significant differences in mean knowledge and practice scores before and after intervention mean of (t (28) =17.32, p < 0.001) and (t (28) = 25.04, p<0.001), respectively. Conclusion: Educational intervention Improved nurses’ knowledge and practice of delirium assessment. Continuous nursing education could improve nurses’ knowledge of delirium assessment and thus quality of patient care.
Keywords: Nurse; Delirium; Assessment; Knowledge; Practice; CAM-ICU